Reducing and preventing health risks related to wastewater and casualty in Kabul city - H. Jahish; N. Mehrdadi; B.Omidvar (Zien Journals, 2021)
Globally, billions of people lack access to adequate sanitation and safe water. Due to the high population of Kabul city and also the great importance of this city, and also considering that no study has been done in this field so far, the present study was conducted to study the Reducing and preventing health risks related to wastewater and casualty in Kabul city. The data, which was collected by the standardized site, visits, questionnaire, and comparing analysis are checked and verified the process. Data entry and processing are done through the application of the Microsoft Excel programs for graphic presentation of data and ArcGIS. According to the advantageous and disadvantageous of stabilization pond, oxidation ditch, and conventional activated sludge, the priority for Kabul city is conventional activated sludge. As Kabul is the capital of Afghanistan, day by day increasing population, and one of the populated cities in the world the budget is available for development therefore conventional activated sludge a good technology, Aerobic decomposition by activated sludge. The retention time was 1.5 hours for primary sedimentation, 6-8 for aeration and 1.5 hours for final sedimentation, and a total of 0.5 days.
Keywords: Health risks; wastewater; Afghanistan; Kabul